2004
DOI: 10.1023/b:thro.0000036027.39353.70
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Concepts in the Triad of Atherosclerosis, Inflammation and Thrombosis

Abstract: Recent developments into antherothrombosis, the leading cause of morbidity and mortality in Western Society, may help to change our treatment strategy to a more casual approach. The composition of the atherosclerotic plaque, rather than the percent stenosis, appears to be a critical predictor for both risk of plaque rupture and subsequent thrombogenicity. A large lipid core, rich in tissue factor (TF) and inflammatory cells including macrophages, and a thin fibrous cap with compromise of its structural integri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0
9

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(79 citation statements)
references
References 44 publications
0
70
0
9
Order By: Relevance
“…Plaque disruption may result in mural thrombi. Such thrombi may be the main contributor of progression of atherosclerosis [28] . In our present study, we found that thrombin could induce CTGF expression in VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Plaque disruption may result in mural thrombi. Such thrombi may be the main contributor of progression of atherosclerosis [28] . In our present study, we found that thrombin could induce CTGF expression in VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical consequences are also rather similar: insufficient maturation or a need for intervention or access abandonment. In fact, thrombosis, atherosclerosis, and inflammation form a pathogenic continuum in cardiovascular disease (15,16). Inflammatory mechanisms upregulate procoagulants, downregulate anticoagulants, and inhibit fibrinolysis, resulting in prothrombotic states (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, thrombosis, atherosclerosis, and inflammation form a pathogenic continuum in cardiovascular disease (15,16). Inflammatory mechanisms upregulate procoagulants, downregulate anticoagulants, and inhibit fibrinolysis, resulting in prothrombotic states (15)(16)(17). Furthermore, acquired coagulation abnormalities (i.e., elevated factor VIII:C level, short thrombin time, and high fibrinogen and D-dimer levels) were frequent in our patients with ESRD (Table 3) and failed to differentiate problems in access thrombosis or stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Plaque rupture is thought to be responsible for the majority of acute coronary syndromes, which in turn are the major causes of morbidity and mortality in coronary artery disease. 87,88 MMPs secreted by macrophages and SMCs in the shoulder regions of the plaque degrade collagens in the fibrous cap rendering the plaque vulnerable to rupture. [89][90][91][92] Fibrillar collagen monomers are cleaved into fragments that are ¼ and ¾ of the length of the native full-length molecules following cleavage at a bond between glycine and isoleucine by the collagenases (MMPs 1, 8, and 13).…”
Section: Collagens and Atherosclerotic Complicationsmentioning
confidence: 99%